An Insight on the Electrocatalytic Mechanistic Study of Pristine Ni MOF (BTC) in Alkaline Medium for Enhanced OER and UOR. Issue 19 (27th July 2018) - Maruthapandian, Viruthasalam; Kumaraguru, Shanmugasundaram; Mohan, Subramanian; Saraswathy, Velu; Muralidharan, Srinivasan
Abstract: Hydrogen production plays a major role in technologies for renewable energy storage. Water and urea electrolysis (WE, UE) are promising processes in this regard. The oxygen evolution reaction (OER) and urea oxidation reaction (UOR), respectively, are limiting the efficiency of the overall process. As catalysts for these reactions, metal‐organic frameworks (MOF) have gained increasing attention due to their combinations and co‐existence of metal and organic moiety properties. Here, we investigated the catalytic behavior of Ni MOF (1, 3, 5‐Benzenetricarboxylic acid (BTC)) towards OER and UOR in alkaline medium on carbon paper (CP) as a support. The Ni MOF exhibits 346 mV overpotential (η) at a current density of 10 mA cm −2, 79.03 A g −1 specific‐mass activity at 400 mV of η than compared to wet chemically prepared (WCP) NiO and RuO2 for OER in 1 M KOH. Meanwhile, ≈230 mV of η at 10 mA cm −2 current density with appreciable stability for 12 hours for Ni MOF in 30 % KOH was also observed. For UOR in UE, Ni MOF shows an onset potential of 1.34 V vs. RHE and 63.15 mA cm −2 current density at 1.5 V vs RHE in 1 M KOH in the presence of 1 M urea. The observed results of OER and UOR catalytic behavior are better than wet chemically prepared (WCP) NiO and noble benchmark RuO2 catalyst under identical conditions. The results suggested that the MOF plays a major role in enhancing the catalytic activity by the facile formation of Ni(OH)2 /NiOOH, stability and electronic properties due to their porous and interconnected structure. Abstract : The electrocatalytic outlook of Ni containing MOF 1, 3, 5‐Benzenetricarboxylic acid (BTC) for enriched performance towards oxygen evolution reaction and urea oxidation reaction in alkaline medium is investigated and discussed elaborately.